Acute acetaminophen (paracetamol) ingestion improves time to exhaustion during exercise in the heat. Issue 1 (28th October 2013) - Mauger, Alexis R.; Taylor, Lee; Harding, Christopher; Wright, Benjamin; Foster, Josh; Castle, Paul C.
New Findings What is the central question of this study? Acetaminophen (paracetamol) is an analgesic and antipyretic, which has been shown to improve self‐paced cycling performance through a reduction in pain. We sought to ascertain whether acetaminophen could improve time to exhaustion during exercise in the heat through its antipyretic action. What is the main finding and its importance? An acute dose of acetaminophen allowed participants to cycle significantly longer in hot conditions by a mean of 4 min (+17%). This was accompanied by significantly lower core, skin and body temperature, and participants found the exercise less of a thermal strain. These findings suggest that acetaminophen may reduce the thermal challenge of exercise in hot conditions. Acetaminophen (paracetamol) is a commonly used over‐the‐counter analgesic and antipyretic and has previously been shown to improve exercise performance through a reduction in perceived pain. This study sought to establish whether its antipyretic action may also improve exercise capacity in the heat by moderating the increase in core temperature. On separate days, 11 recreationally active participants completed two experimental time‐to‐exhaustion trials on a cycle ergometer in hot conditions (30°C, 50% relative humidity) after ingesting a placebo control or an oral dose of acetaminophen in a randomized, double‐blind design. Following acetaminophen ingestion, participants cycled for a significantly longer period of time (acetaminophen, 23 ± 15 min versus placebo, 19 ± 13 min; P= 0.005; 95% confidence interval = 90–379 s), and this was accompanied by significantly lower core (−0.15°C), skin (−0.47°C) and body temperatures (0.19°C; P < 0.05). In the acetaminophen condition, participants also reported significantly lower ratings of thermal sensation (−0.39; P= 0.015), but no significant change in heart rate was observed (P > 0.05). This is the first study to demonstrate that an acute dose of acetaminophen can improve cycling capacity in hot conditions, and that this may be due to the observed reduction in core, skin and body temperature and the subjective perception of thermal comfort. These findings suggest that acetaminophen may reduce the thermoregulatory strain elicited from exercise, thus improving time to exhaustion.